Strategic uncertainty and firm performance: The mediating role of competitive intelligence practices - Yap, CS Yap; Md Zabid; Dewi (World Scientific Publishing Co., 2013)
To overcome the problems of managing too much information and curating for the valuable content, DuPont’s research, business, regulatory, manufacturing, legal, and marketing teams increasingly rely on the corporate library’s competitive intelligence (CI) team to keep up with the latest Key Intelligence Topics (KITs) affecting their strategic goals and their decision-making processes. To meet the growing demand for CI news with constrained resources, the library CI team and the software application team designed and built CIntell, a user-friendly collection of technologies and services to harvest, store, curate, and publish secondary CI information. Using exclusively open source technologies (including Weka, Rome, MySQL, Solr), CIntell automatically harvests, filters, de-duplicates, tags, classifies, and stores public and subscribed secondary information in a structured database including news, research publications, patents, government reports, and web information. The CIntell web-based user interface facilitates searching, reviewing, organising, curating, and publishing CI news of interest to a project’s owners. Implementation of CIntell has more than tripled the CI newsletter productivity of the library CI team and reduced the news clutter by more than half compared to using traditional alerting tools and sporadic DIY searching.